Information asymmetry, trade, and drilling: evidence from an oil lease lottery. (9th August 2021) - Brehm, Paul A.; Lewis, Eric
Abstract: We exploit a government oil lease lottery that randomly assigned leases to individuals and firms. We examine how initial misallocation affected trade, drilling, and production outcomes. When parcels are far from existing production, leases won by individuals have similar drilling and production outcomes as those won by firms. However, for parcels close to existing production, we find that leases are about 50% less likely to be drilled when they are won by firms. We find evidence that information asymmetries drive these results.